Bisphenols induce human genomic damage and modulate HERVs/env expression. (1st September 2022) - Ruberto, Stefano; Santovito, Alfredo; Simula, Elena R.; Noli, Marta; Manca, Maria A.; Sechi, Leonardo A.
Abstract: Bisphenol A (BPA), a recognized endocrine‐disrupting chemical, is used in the production of epoxy and polycarbonate resins. Since human exposure to BPA has been associated with increased cancer susceptibility, the market has shifted to products often labeled as " BPA free " containing BPA analogs such as bisphenol F (BPF) and bisphenol S (BPS). However, the European legislation on BPF and BPS is still unclear. This study analyzed the effects of BPA, BPF, and BPS exposure on human peripheral blood mononuclear cells by using in vitro micronucleus assay. Furthermore, it investigated the impact of bisphenols exposure on human endogenous retroviruses (HERVs) expression, which is implicated with the pathogenesis of several human diseases. The micronucleus assay revealed a significant genotoxic effect in peripheral blood cells after exposure to BPA and BPF at concentrations of 0.1, 0.05, and 0.025 μg/ml, and to BPS at 0.1 and 0.05 μg/ml. In addition, BPA exposure seems to upregulate the expression of HERVs, while a downregulation was observed after BPF and BPS treatments. Overall, our data showed the toxic effect of BPA and its analogs on circulating cells in the blood and demonstrated that they could modulate the HERVs expression.